Screening of Pea (Pisum sativum L.) Germplasm for Growth, Yield and Resistance Against Powdery Mildew under Mid-hill Conditions of Himachal Pradesh - Kumar, Rakesh; Kumar, Manish; Kumar, Sandeep; Kumar, Anil (International Journal of Bio-resource and Stress Management, 2023)
Fifty four genotypes of pea including four check cultivars were evaluated for various important horticultural traits in a RCBD with three replications during Rabi, 2010-11. The observations were recorded on days to first flower (number), node at which the first flower appear (number), number of pods plant-1, pod length (cm), number of seeds pod-1, shelling %, days to marketable maturity (number), pod yield (kg plot-1), pod yield (q ha-1), TSS (°B), total phenols (g 100 g-1) and powdery mildew severity (%). Analysis of variance showed significant differences among all the genotypes for all the characters under study. In this study 4 genotypes were found earliest among all. Three genotypes were found superior to yield and yield contributing traits when compared with the performance of the check cultivars. While 23 genotypes performed better than the check cultivars among quality traits viz., total sugars (%), total soluble solids (°B) and phenol content (g 100 g-1). Similarly, 18 genotypes had shown a resistant reaction to powdery mildew severity (%). It is concluded that genotypes 10/PMVAR-3, 10/PMVAR-4, 10/PMVAR-5, 9/PMVAR-7, AG-12, IC-381058 and VP-433 were superior over other entries and over standard checks for yield, quality and other important horticultural traits. 10/PMVAR-5 was found superior to checks in most of characters like pod yield (q ha-1), number of pods plant-1, shelling %, total sugars (%) and total soluble solids (°B). Thus it is recommended for further multi-location testing in the different regions of state.